Adaptive solar panel - overview and conceptual design - Wan Abdul Hamid, Wan Luqman Hakim; Basharuddin, Nurul 'Ilya; Sukindar, Nor Aiman (IOP Publishing Ltd, 2022)
Renewable energy should reach its maximum usage capacity, around 20%, by 2025, as laid out by the Malaysian government to achieve the seventh Sustainable Development Goals (SDG): Affordable and clean energy. Many actions have been implemented to support the idea, including the development of solar energy panels in large photovoltaic installation. However, the installations require a wide area of land, and the efficiency offered is limited due to their fixed position. The efficiency of solar panels in absorbing the light from the sun is important to increase the energy supply. Several designs of the adaptive solar panel were developed by researchers, but the installation costs are high due to the components used. Commonly used actuators to move the solar panels are motor (DC motor, stepper motor, servo motor) that actuate according to the signals from photosensor, programming logic control (PLC), or microcontroller. Herein, the development of an Adaptive Solar Panel (ASP) is studied. SMA with high recoverability when it is strained is introduced as an actuator that capable of generating large actuation when heated to move the solar panel. In discovering the potential of SMA wire, a modern environmental-friendly design with six layers of solar panels with a rotational support system was designed in this study. In future work, the SMA wire actuation will be evaluated by computational simulation method using LS-Dyna.